2012
DOI: 10.1186/1746-160x-8-33
|View full text |Cite
|
Sign up to set email alerts
|

Use of dermal-fat grafts in the post-oncological reconstructive surgery of atrophies in the zygomatic region: clinical evaluations in the patients undergone to previous radiation therapy

Abstract: IntroductionGrafting of autologous adipose tissue can be recommended in some cases of facial plastic surgery. Rhabdomyosarcoma is a type of cancer that can also affect the orbit. Enucleation of the eye can cause atrophy of the corresponding hemiface and decreased orbital growth.Case reportWe report a case of a female patient with a medical history of surgical enucleation of the right eyeball, who had received rhabdomyosarcoma radiation therapy in her youth. The patient presented with a depression in the right … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Their grafts were survived with very good final cosmetic results. The current study is in agreement with the previous study done by Inchingolo et al 14 We thought that the graft survived even in the irradiate patients due to the dermal component of the graft and its proangiogenic properties with high ability of graft perfusion reestablishment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Their grafts were survived with very good final cosmetic results. The current study is in agreement with the previous study done by Inchingolo et al 14 We thought that the graft survived even in the irradiate patients due to the dermal component of the graft and its proangiogenic properties with high ability of graft perfusion reestablishment.…”
Section: Discussionsupporting
confidence: 93%
“…This is due to the excessive release of cytokines that cause fibrosis and aberrant vascular tissue. 14 Despite these factors, studies have shown good results with FDFG in patients who have previously undergone radiation therapy. 14 In the current study, 2 patients with preauricular depression defects who underwent previous radiation therapy were treated with FDFG to reconstruct the soft tissue defects (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Reconstructive surgery could be indicated in areas deeply atrophic, following the radiotherapy. 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
“…It's important to underline that the bone modification is a physiological process that combines the osteogenesis and the bone remodelling (13)(14)(15). In such cases where a guided bone regeneration is needed, the bone regeneration can be improved by using platelets concentrates (16,17), new generation of biomaterials, new surgical techniques (18)(19)(20)(21)(22)(23)(24)(25) or innovative devices.…”
Section: Resultsmentioning
confidence: 99%